Routine data processing in earthquake seismology : with sample data, exercises and software / Jens Havskov, Lars Ottemöller. - Havskov, J. (Springer, 2010)
The purpose of this book is to get a practical understanding of the most common processking techniques in earthquake seismology, The book deals with manual methods and computer assisted methods. Each topic will be introduced with the basic theory followed by practical examples and exercises. There are manual exercises entrirely based on the printed material of the book, as well as computer exercised based on public domain software. Most exercises are computer based. The softward used, as well as all test data are available from http://extras.springer.com.